Preliminary toxicity test and phytochemical screening of Sargassum polycystum crude extracts from marine macroalgae - Daud Norhayati, Mohd Noor Nor Nafizah, Alimon Hasimah, Abdul Rashid Nursuhaidah, (N/A, 2015)
Preliminary toxicity test and phytochemical screening of Sargassum polycystum crude extracts from marine macroalgae by Daud Norhayati, Mohd Noor Nor Nafizah, Alimon Hasimah, Abdul Rashid Nursuhaidah,